What's on your hard drive?. - O'Hanlon, Charlene (ACM queue : architecting tomorrow's computing., 2006)
As the year draws to an end, we would like to thank all of our readers who have submitted to WOYHD. Over the past 12 months we've seen a wide variety of tools mentioned, and, come 2007, we would like to see a lot more of the same. So log on to our Web site at http://www.acmqueue.com and send us your rants, raves, and more new tools that you absolutely can't live without---or can't stand to use. As further incentive, if we publish your submission, you'll be starting off the New Year with a brand new Queue coffee mug!